TRICKSTER ARCHETYPE AS SEEN IN HARRY POTTER MOVIES THE FOURTH AND THE FIFTH SERIES - Hana Tirtaningtias; Dwi Budi Setiawan (Linguistics and Literature Students' Journal, 2021)
This research discusses two series of Harry Potter’s movies entitled “Harry Potter and The Goblet of Fire” the fourth series and “Harry Potter and The Order of the Phoenix” the fifth series. This research aims to show the portrayal of the trickster archetype that could be seen in some characters inside the movies. In this research, the writers apply descriptive qualitative method. The data are taken from the scenes inside of the movies and the dialogue. In this research, the writers apply Archetype theories by Carl Jung and movie analysis theory by Pratista. In analysing the movie, the writer also uses a table by Nurmaily. The result of the research shows that Harry Potter Movies, the fourth series and the fifth series written by J.K Rowling, depict the existence of trickster archetype. There are two characters, the supporting characters, that portrayed the characterization of a trickster archetype, They are George and Fred. They reveal the characterization which are the characteristics of trickster archetype, such as mischievous, smart, cunning and creative; and disobedient.Keywords: Archetype, literary work, trickster, Harry Potter